The Impact of Co-Viewing on Attachment Between Parents and Children - Winda Gunarti; Raden Sri Martini Meilanie; Happy Karlina Marjo (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
Watching (screen viewing) has become a common activity carried out in early childhood. Generally, children aged 2-5 years do watching activities for about 3 hours more a day. This study aims to see how watching activities together can increase attachment between parents and children. This study uses a qualitative approach that produces descriptive data in the form of written words or messages from people and observed behavior and uses observation, interview, or document review methods. Observations were made on co-viewing activities carried out by a child and his parents at home because this activity was found to have an impact on the attachment relationship between the two parties. The selected respondent is one of the parents of a 3-year-old child (G) (Mrs. B). Data collection was carried out at the residence of Mrs. B and G for several weeks. The data collection techniques used were interviews and observations. The results show that watching activities together has a positive impact on the attachment between parents and early childhood. This can be seen from the characteristics of the safe attachment that children have after watching the activities together, after previously the attachment they had characterized as an avoidant attachment. It can also be seen how parents have a big role in the formation of this secure attachment. Keywords: secure attachment, co-viewing watching activities, parent-children interaction References: Arianda, V., Salim, I. K., & Ruzain, R. B. (2022). Secure Attachment (Kelekatan Aman) Ibu dan Anak dengan Perkembangan Sosial Emosional Pada Anak. Journal of Islamic and Contemporary Psychology (JICOP), 1(2), 67–74. https://doi.org/10.25299/jicop.v1i2.8603 Barr, R., Zack, E., Garcia, A., & Muentener, P. (2008). Infants’ Attention and Responsiveness to Television Increases with Prior Exposure and Parental Interaction. Infancy, 13(1), 30–56. https://doi.org/10.1080/15250000701779378 Belsky, J., & Nezworski, T. (1988). Clinical Implications of Attachment. L. Erlbaum Associates. https://books.google.co.id/books?id=NY1AQTAkhKAC Crain, W. C. (2011). Theories of Development: Concepts and Applications. Prentice Hall. https://books.google.co.id/books?id=z0ZeRwAACAAJ Dearing, E., McCartney, K., Weiss, H. B., Kreider, H., & Simpkins, S. (2004). The promotive effects of family educational involvement for low-income children’s literacy. Journal of School Psychology, 42(6), 445–460. https://doi.org/10.1016/j.jsp.2004.07.002 Elias, N., & Sulkin, I. (2017). YouTube viewers in diapers: An exploration of factors associated with amount of toddlers’ online viewing. Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 11(3). https://doi.org/10.5817/CP2017-3-2 Haridakis, P., & Hanson, G. (2009). Social Interaction and Co-Viewing With YouTube: Blending Mass Communication Reception and Social Connection. Journal of Broadcasting & Electronic Media, 53(2), 317–335. https://doi.org/10.1080/08838150902908270 Hiniker, A., Suh, H., Cao, S., & Kientz, J. A. (2016). Screen Time Tantrums: How Families Manage Screen Media Experiences for Toddlers and Preschoolers. Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 648–660. https://doi.org/10.1145/2858036.2858278 Holloway, D., Green, L., & Livingstone, S. (2013). Zero to eight: Young children and their internet use (pp. 10–13). LSE, London and EU Kids Online. Iskandar, T. P., & Nadhifa, R. A. F. (2021). Fenomena Penggunaan Youtube Channel Pada Anak Usia Dini di Masa Pendemic Covid-19 [The Phenomenon of Using Youtube Channels in Early Childhood During the Covid-19 Pandemic.]. Jurnal Ilmiah LISKI (Lingkar Studi Komunikasi), 7(2). http://journals.telkomuniversity.ac.id/liski Kabali, H. K., Irigoyen, M. M., Nunez-Davis, R., Budacki, J. G., Mohanty, S. H., Leister, K. P., & Bonner, R. L. (2015). Exposure and Use of Mobile Media Devices by Young Children. PEDIATRICS, 136(6), 1044–1050. https://doi.org/10.1542/peds.2015-2151 Keene, J. R., Rasmussen, E. E., Berke, C. K., Densley, R. L., Loof, T., Adams, R. B., Mumma, G. H., & Marshall, A. (2019). The effect of plot explicit, educational explicit, and implicit inference information and coviewing on children’s internal and external cognitive processing. Journal of Applied Communication Research, 47(2), 153–174. https://doi.org/10.1080/00909882.2019.1581367 Kirkorian, H. L., Pempek, T. A., Murphy, L. A., Schmidt, M. E., & Anderson, D. R. (2009). The Impact of Background Television on Parent-Child Interaction. Child Development, 80(5), 1350–1359. https://doi.org/10.1111/j.1467-8624.2009.01337.x Lemish, D., & Rice, M. L. (1986). Television as a talking picture book: A prop for language acquisition. Journal of Child Language, 13(2), 251–274. Cambridge Core. https://doi.org/10.1017/S0305000900008047 Moleong, L. J., & Surjaman, T. (1989). Metodologi penelitian kualitatif. Remadja Karya. https://books.google.co.id/books?id=YXsknQEACAAJ Papalia, D. E., Olds, S. W., & Feldman, R. D. (2007). Human Development. McGraw-Hill. https://books.google.co.id/books?id=tGHmxgEACAAJ Pempek, T. A., Demers, L. B., Hanson, K. G., Kirkorian, H. L., & Anderson, D. R. (2011). The impact of infant-directed videos on parent–child interaction. Journal of Applied Developmental Psychology, 32(1), 10–19. https://doi.org/10.1016/j.appdev.2010.10.001 Pempek, T. A., Kirkorian, H. L., & Anderson, D. R. (2014). The Effects of Background Television on the Quantity and Quality of Child-Directed Speech by Parents. Journal of Children and Media, 8(3), 211–222. https://doi.org/10.1080/17482798.2014.920715 Pires de Sá, F. (2015). The co-viewing 2.0: Detaching from History and Applying in the New Media Age. КУЛТУРА/CULTURE, 5(11). Rachmat, I. F. (2019). Pengaruh Kelekatan Orang Tua Dan Anak Terhadap Penggunaan Teknologi Digital Anak Usia Dini [The Influence of Attachment of Parents and Children to the Use of Digital Technology in Early Childhood]. Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 6(1), 14–29. https://doi.org/10.32534/jjb.v6i1.546 Santrock, J. W. (2009). Child Development. McGraw Hill. https://books.google.co.id/books?id=I58GLwAACAAJ Sims, C. E., & Colunga, E. (2013). Parent-Child Screen Media Co-Viewing: Influences on Toddlers’ Word Learning and Retention. Cognitive Science, 35. Skaug, S., Englund, K. T., & Wichstrøm, L. (2018). Young children’s television viewing and the quality of their interactions with parents: A prospective community study. Scandinavian Journal of Psychology, 59(5), 503–510. https://doi.org/10.1111/sjop.12467 Tamis-LeMonda, C. S., & Rodriguez, E. T. (2015). Parents’ Role in Fostering Young Children’s Learning and Language Development. In Encyclopedia of the Centre of Excellence for Early Childhood Development (CEECD). Toth, S. L., & Cicchetti, D. (2013). A Developmental Psychopathology Perspective on Child Maltreatment. Child Maltreatment, 18(3), 135–139. https://doi.org/10.1177/1077559513500380 Vaala, S. E., & Hornik, R. C. (2014). Predicting US Infants’ and Toddlers’ TV/Video Viewing Rates: Mothers’ Cognitions and Structural Life Circumstances. Journal of Children and Media, 8(2), 163–182. https://doi.org/10.1080/17482798.2013.824494 Vandewater, E. A., Bickham, D. S., & Lee, J. H. (2006). Time Well Spent? Relating Television Use to Children’s Free-Time Activities. Pediatrics, 117(2), e181–e191. https://doi.org/10.1542/peds.2005-0812 Zimmerman, F. J., Christakis, D. A., & Meltzoff, A. N. (2007). Television and DVD/Video Viewing in Children Younger Than 2 Years. Archives of Pediatrics & Adolescent Medicine, 161(5), 473–479. https://doi.org/10.1001/archpedi.161.5.473